PENINGKATAN PRODUKTIVITAS GURU DAN LEMBAGA PENDIDIKAN TENAGA KEPENDIDIKAN PADA ERA GLOBAL - Subandowo Subandowo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2009)
In this globalization era, teacher plays an important role, because a teacher has a noble duty of producing qualified human resource. This has put teachers at the following roles: 1) agent of change. In this fast transformation era teacher can act as an effective agent of change; 2) Inspirer of tolerance and mutual understanding which is required of mankind through education process; and 3) professional educator. In the globalization era, schools are required to play the role as centre of learning. This means that the role of teacher is very important in preparing highly competitive learners. It is therefore imperative for teachers to improve their professionalism through upholding their educational qualification both in term of academic and professional competence. With it is expected that the quality of their performance and teaching achievement will improve. Key words : Teacher’s productivity, institute for teacher’s training, global era